2013
DOI: 10.1371/journal.pone.0073635
|View full text |Cite
|
Sign up to set email alerts
|

Lrig2-Deficient Mice Are Protected against PDGFB-Induced Glioma

Abstract: BackgroundThe leucine-rich repeats and immunoglobulin-like domains (LRIG) proteins constitute an integral membrane protein family that has three members: LRIG1, LRIG2, and LRIG3. LRIG1 negatively regulates growth factor signaling, but little is known regarding the functions of LRIG2 and LRIG3. In oligodendroglial brain tumors, high expression of LRIG2 correlates with poor patient survival. Lrig1 and Lrig3 knockout mice are viable, but there have been no reports on Lrig2-deficient mice to date.Methodology/Princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 40 publications
2
59
1
1
Order By: Relevance
“…13 Thus, the HPSE2 gene product may modify heparanase 1 activity within ganglia. Our observation that LRIG2 was also present in pelvic ganglia, combined with a report that LRIG2 modifies growth factor signaling in glioma cells, 24 suggests that LRIG2 may operate in similar biologic pathways as heparanase 2. If autonomic nerve function is perturbed, then the cyclic low-pressure storage of urine and complete bladder emptying will be impaired.…”
supporting
confidence: 74%
“…13 Thus, the HPSE2 gene product may modify heparanase 1 activity within ganglia. Our observation that LRIG2 was also present in pelvic ganglia, combined with a report that LRIG2 modifies growth factor signaling in glioma cells, 24 suggests that LRIG2 may operate in similar biologic pathways as heparanase 2. If autonomic nerve function is perturbed, then the cyclic low-pressure storage of urine and complete bladder emptying will be impaired.…”
supporting
confidence: 74%
“…The antibodies were obtained from various sources as follows: anti-phosphotyrosine (p-Tyr) and anti-phospho-TrkB (p-Tyr 705) were from Santa Cruz Biotechnology, anti-TrkB was from BD Biosciences Pharmingen, rabbit polyclonal anti-Lrig1 extracellular domain (gift from Dr. Satoshi Itami, University of Osaka, Osaka, Japan) [19,24], anti-Lrig1 intracellular domain was from R&D Systems, anti-HA was from Roche, rabbit polyclonal anti-Lrig2-147 [58] and rabbit polyclonal anti-Lrig3-207 were from Dr. Håkan Hedman laboratory (Umeå University, Sweden), antiphospho-MAPK (Thr-202/Tyr-204) was from New England Biolabs, anti-bIII-tubulin was from Promega, anti-MAP-2, antiS100b, and anti-Flag (M2) were from Sigma, and anti-ubiquitin was from Millipore.…”
Section: Antibodiesmentioning
confidence: 99%
“…Less is known regarding the specific molecular functions of LRIG2 and LRIG3 although they do not appear to have the same global ability to decrease growth factor receptor expression. LRIG2 has no significant effect on the expression of EGFR, ErbB2 (Rafidi et al , 2013) or PDGFRα/β (Rondahl et al , 2013) while LRIG3 has been found to oppose LRIG1 (Rafidi et al , 2013) and increase expression of ErbBs 1-4 (Rafidi et al , 2013). LRIG1 limits LRIG3 action by promoting its proteolytic degradation, highlighting a complex cross-talk amongst LRIG family members (Rafidi et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…LRIG1 has been identified as a negative regulator of several receptor tyrosine kinases including ErbBs 1-4 (Laederich et al , 2004, Gur et al , 2004), EGFRvIII (Stutz et al , 2008), Met (Shattuck et al , 2007), Ret (Ledda et al , 2008) and PDGFR-α (Rondahl et al , 2013). With the exception of the Ret receptor and the PDGFR-α (for which it was not examined), LRIG1 has been found to increase the ubiquitination and decrease the half –life of its targets.…”
Section: Introductionmentioning
confidence: 99%